Remittances and Economic Growth: Evidence from Ethiopia, Kenya, and Uganda - Zerihun, Mulatu F (African Human Mobility Review, 2021)
The purpose of this study is to analyze the possible effect of international remittanceson the economic growth in three selected economies of Intergovernmental Authorityon Development (IGAD) member countries, namely, Ethiopia, Kenya, and Uganda.Remittance inflows have emerged as a key link between human mobility anddevelopment. However, empirical findings on the nexus between remittances andeconomic growth are either conflicting or at most mixed. This paper explores theeffects of remittances from international migration inflows on the economic growth ofthree IGAD member countries. The study uses quantitative analysis that encompassesthe above-mentioned countries using the World Bank’s annual data from 1990 to 2017.The novelty of this study is that it uses different approaches to solicit the short-runand the long-run nexus between economic growth and remittance flow. The pooledestimation result from fully modified least squares (FMOLS) shows that the logarithmof remittances impacts the dependent variable, economic growth, positively but notstatistically significant. The Kao panel residual cointegration test shows that the nullhypothesis is not sufficiently supported by the data. There is a statistically significantlong-run relationship between the variables in the series.